Paper-Based Point-of-Care Testing of SARS-CoV-2 - Jia, Yuan; Sun, Hao; Tian, Jinpeng; Song, Qiuming; Zhang, Wenwei (Frontiers in Bioengineering and Biotechnology, 2021)
The COVID-19 pandemic has resulted in significant global social and economic disruption. The highly transmissive nature of the disease makes rapid and reliable detection critically important. Point-of-care (POC) tests involve performing diagnostic tests outside of a laboratory that produces a rapid and reliable result. It therefore allows the diagnostics of diseases at or near the patient site. Paper-based POC tests have been gaining interest in recent years as they allow rapid, low-cost detection without the need for external instruments. In this review, we focus on the developments of paper-based POC devices for the detection of SARS-CoV-2. The review first introduces the principles of detection methods that are available to paper-based devices. It then presents the state-of-the-art paper devices and their analytical performances, as well as the advantages and drawbacks among methods are discussed. Finally, limitations of the existing devices are discussed, and prospects are given with the hope to identify research opportunities and direction in the field. We hope this review will be helpful for researchers to develop a clinically useful and economically efficient paper-based platform that can be used for rapid, accurate on-site diagnosis to aid in identifying acute infections and eventually contain the COVID-19 worldwide outbreak.